The influence of cryopreserved chorionic and amniotic membrane on the structure of modeled trophic ulcers. - Roenko, A. A.; Prokopyuk, V. Yu.; Volina, V. V.; Shevchenko, N. A.; Falko, O. V.; Prokopyuk, O. S. (Морфологія / Morphologia / Morfologìâ, 2015)
Background. Treatment of trophic ulcers is one of the most difficult and relevant problem of the modern medicine. Trophic ulcers are diagnosed in 2% of the population in developing countries. Objective. The purpose of this research was to study morphological effects of cryopreserved amniotic and chorionic membranes on the healing of trophic ulcers. Methods. Cryopreserved fetal membranes and Solcoseryl ointment were applied for 24 hours with 48 hour break four times on an experimental model of ulcers. Histological analysis of mice skin was performed on days 3rd (the time of wound formation), 7th, 14th, 21st, 28th and 35th after the beginning experiment. Results. When treating ulcers by the standard traditional method using a dressing with Solcoseryl ointment histological examination revealed the presence of coarse trophic disorders, which disappeared slowly because of abnormal regeneration. The use of cryopreserved fragments of chorionic and amniotic membranes stimulated an active proliferation and differentiation of fibroblasts along with angiogenesis, which promotes the growth of granulation tissue, further regeneration of the epithelium together with the cleansing of ulcer surface and fibrous tissue transformation. Conclusion. In the trophic ulcer model we have showed that the use of cryopreserved fetal membranes leads to an accelerated healing of ulcers.